Incidence of Maltreatment of Aboriginal Children Reported to Youth Protection in Quebec: Intercultural Comparisons - Tourigny, Marc; Domond, Pascale; Trocmé, Nico; Sioui, Bruno; Baril, Karine (First Peoples Child & Family Review, 2007)
The purpose of the study is to examine reported cases of maltreatment in Aboriginal children and compare them with cases involving non-Aboriginal children based on a sample of such cases reported to Youth Protection services in Quebec. Results indicate that, in Quebec, cases involving Aboriginal children compared with cases for non-Aboriginal children are characterized by living situations such as subsidized housing, substance abuse in parents, an increased number of children in the family, the fact that a case reported was a ‘social emergency’and that a case was less reported by the mother. Intervention plans with Aboriginal families and suggestions for future research are discussed.